Konsepsi Strategis Pengembangan Wakaf Produktif melalui Investasi Berbasis Syariah - An'im Fattach; Maskun Maskun (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2022)
Waqf is a unique Islamic economic instrument based on its function on the elements of virtue (birr), goodness (i'hsan) and brotherhood (u'khuwah). The distinguishing characteristic of waqf is that when the waqf is fulfilled, there is a shift in private ownership towards the ownership of Allah SWT which is expected to be eternal, providing sustainable benefits. Through waqf, it is hoped that there will be a process of distributing benefits for the wider community, from private benefits to social benefits. This study uses library research with descriptive qualitative methods, namely, first by recording all findings regarding the concept of global supply and demand in each research discussion obtained in the literature and sources, and or the latest findings regarding productive waqf. and investment. The conclusion of this study is that the real strategy in developing productive waqf lands is as follows, that Nazhir must establish business partnerships with other parties who have capital and business interests in accordance with the existing strategic land position with high commercial value. This collaboration is in order to mobilize all the economic potential of the waqf lands. Once again, it must be emphasized that the system of cooperation with third parties must still follow the Sharia system, both by way of musharaka and mudharabah as previously mentioned.